Comparison of letrozole with gonadotropins and letrozole_gonadotropin combination for ovulation induction in PCOS women after clomiphene citrate failure - M. Majeed, Bushra (Tikrit Journal of Pharmaceutical Sciences, 2023)
The aim of this study is to compare the efficacy of letrozole with gonadotropin and letrozole plus gonadotropin for ovulation induction in PCOS women after clomiphene citrate failure, Seventy eight women with PCO failed to conceive with clomiphene citrate divided in to three groups A,B,C treated with letrozole tablet, , letrozole plus follicular stimulating hormone and follicular stimulating hormone injection alone respectively for ovulation induction..Results: ovulation rate was (65.4%),(76.9%) and(76.9%) in group A,B &C respectively, pregnancy rate in study groups were (50%),(69.2%)and(65.4%) in A,B,&C respectivelyConclusion: Letrozole appears to be a suitable ovulation inducing agent in PCOS women with CC failure and significant higher pregnancy rate was observed in letrozole co treatment with gonadotropins as compared to other two protocoles